CIVES - Citizens Towards Sustainability. Emblematic results of a research - Sara Bornatici; Orietta Vacchelli (Firenze University Press, 2021)
L. n. 92/2019 introduced the transversal teaching of civic education in schools of all levels from the 2020-2021 school year. This contribution, without any claim to being exhaustive, proposes an interpretative reflection starting from some data that emerged in the context of the CIVES research (CIttadini VErso la Sostenibilità) which started from the training course on sustainable development aimed at the referring teachers of civic education of 51 Brescia institutes. The observations collected in the group debates highlighted fundamental contextual data for setting educational interventions, in an overall situation that appears very heterogeneous. Culture of sustainability and solidarity citizenship constitute two possible interpretations of the legislative proposal, taken for the training of teachers.   CIVES - CIttadini VErso la Sostenibilità. Esiti emblematici di una ricerca La L. n. 92/2019 ha introdotto dall'anno scolastico 2020-2021 l'insegnamento trasversale dell'educazione civica nelle scuole di ogni ordine e grado. Il presente contributo, senza alcuna pretesa di esaustività, prospetta una riflessione interpretativa a partire da alcuni dati emersi nell'ambito della ricerca CIVES (CIttadini VErso la Sostenibilità) che ha preso le mosse dal corso di formazione in tema di sviluppo sostenibile rivolto ai docenti referenti di educazione civica di 51 istituti bresciani. Le osservazioni raccolte nei dibattiti di gruppo hanno evidenziato dati contestuali fondamentali per impostare interventi educativi, in una situazione complessiva che appare assai eterogenea. Cultura della sostenibilità e cittadinanza solidale configurano due possibili chiavi di lettura della proposta legislativa, assunte per la formazione dei docenti.